The Effect of the Familiarity of a Survey Sender on Response Outcomes in a Large-Scale Survey of Emergency Medical Services Agencies. Issue 3 (September 2021) - Millar, Morgan M.; Hewes, Hilary A.; Genovesi, Andrea L.; Ely, Michael; Green, Braden; Schmuhl, Patricia; Polzin, Kjelsey; Santana, Carolina Roberts; Minkler, Marc; Olson, Lenora M.
Survey response is higher when the request comes from a familiar entity compared to an unknown sender. Little is known about how sender influences response to surveys of organizations. We assessed whether familiarity of the sender influences response outcomes in a survey of emergency medical services agencies. Emergency medical services agencies in one U.S. state were randomly assigned to receive survey emails from either a familiar or unfamiliar sender. Both deployment approaches were subsequently used nationwide, with each state selecting one of the two contact methods. Experimental results showed that requests from the familiar sender achieved higher survey response (54.3%) compared to requests from the unfamiliar sender (36.9%; OR: 2.03; 95% CI: 1.23, 3.33). Similar results were observed in the subsequent nationwide survey; in states where the familiar sender deployed the survey, 62.0% of agencies responded, compared to 51.0% when the survey was sent by the unfamiliar sender (OR: 1.57; 95% CI: 1.47, 1.67). The response difference resulted in nearly 60 additional hours of staff time needed to perform telephone follow-up to nonrespondents. When surveying healthcare organizations, surveyors should recognize that it is more challenging to obtain responses without a pre-established relationship with the organizations.